Personal alchemy : a handbook of healing and self-transformation - Wolfe, Amber, 1950- (St. Paul, Minn., U.S.A. : Llewellyn, 1993)
Participate in the creation of your own personal and powerful system of healing magick. Contains the secrets of using color and light "Rays" combined with the art of active imagery to personally experience the alchemy of positive self-transformation and empowerment. Explore the alchemical properties of 21 different healing Rays in depth while actively participating in life-changing exercises.
Includes bibliographical references (p. 543-546).
Keywords: Color -- Psychic aspects; Alchemy; Magic